1999
DOI: 10.1128/aac.43.8.2087
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of kasA Analysis to Detection of Isoniazid-Resistant Mycobacterium tuberculosis in Singapore

Abstract: Genotypic analysis of resistance to isoniazid (INH) inMycobacterium tuberculosis is complex due to the various genes potentially involved. Mutations in ketoacyl acyl carrier protein synthase (encoded by kasA) were present in 16 of 160 (10%) INH-resistant isolates (R121K [n = 1], G269S [n = 3], G312S [n = 11], G387D [n = 1]). However, G312S was also present in 6 of 32 (19%) susceptible strains. kasA analysis contributed marginally to the performance of INH genotypic testing in Singapore. The significance of kas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(41 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…These strains might have additional mutations in other codons of the amplified region of katG gene or outside this investigated region or in other genes involved in INH resistance. Furthermore, INH resistance could be due to unknown mechanisms (Lee et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…These strains might have additional mutations in other codons of the amplified region of katG gene or outside this investigated region or in other genes involved in INH resistance. Furthermore, INH resistance could be due to unknown mechanisms (Lee et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Only 33.4 % of mechanisms of resistance to INH have been known. Other researchers have been reported that mutations in promoters of ahpC and kasA gene are important within 12-24 and 10-14 %, respectively [14][15][16]18]. Therefore, these unknown cases of resistance to INH could be detected with assessment of ahpC and kasA gene promoters.…”
Section: Methods Sensitivity For Identification Of Inh-resistant Mtbmentioning
confidence: 96%
“…In addition, mutations in the regulatory region of the inhA gene have been reported in up to 32 % of INH-resistant isolates [14][15][16][17]. Mutations in other genomic regions, such as the promoter of ahpC gene and the kasA gene, have been reported in 12-24 and 10-14 % of INHresistant strains, respectively [14][15][16]18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further expansion must be made of the results of non-mutating strains as research for inhA mutations, point mutations in the aphC-oxyR intergenic region (Wilson and Collins, 1996;Piatek et al, 2000), or mutations in the kasA gene (Mdluli et al, 1998;Lee et al, 1999).…”
mentioning
confidence: 99%